Polis Diraja Malaysia dan pendekatan keselamatan komuniti luar bandar: satu kajian kes di Padang Besar, Perlis - Salehin, Suleiman (2022)
Rural communities are a group of people living in a society that has a close understanding and is constantly connected with one another. The geography of Perlis which is located at the Thai border has made its community stunned by criminal activities and behaviour. The main objective of this study is to look at crime prevention methods by PDRM in rural communities in Padang Besar, Perlis. There are three main objectives outlined in this study which are: (i) Identifying crime prevention and control tasks carried out by PDRM in Padang Besar, Perlis; (ii) Analyze the process of cooperation cooperation process of PDRM and the public and crime prevention and control in the community in Padang Besar; (iii) Identify the effectiveness of crime prevention and control by PDRM to achieve sustainable development in the community in Padang Besar.. Qualitative approach is used in conducting this study. The data was obtained through interview methods with respondents who are members of PDRM and the public in Padang Besar. The findings show that there is no special and specific SOP that PDRM teams should follow in carrying out crime prevention and control tasks for rural communities. In order to fulfil crime prevention and control tasks, the PDRM team at Pa-dang Besar always conducts patrols in the community especially at the Malaysia-Thailand border. The study also found that the relationship between PDRM and the community in Padang Besar is good where the level of willingness of the public to cooperate with the authorities when needed is high. The study also recommended several recommendations that could be considered for the prevention and control of publicncommunity safety.